Education Law and Management Teacher's Professional Ethics in Secondary Schools Delta State Nigeria - Ossai, Anthony Great; Nwabuwe, Sunday Nathaniel (Letiges, 2023)
This study focuses on education law and teacher ethics management in Delta Public Secondary Schools in Nigeria. In this study, a descriptive technique was used. The study group consisted of 473 principals and 14,482 teachers from 473 public high schools in Delta. A sample of 825 respondents (75 principals and 750 teachers) was drawn using a simple random sampling method. This study was based on two research questions and two hypotheses. A 15-item questionnaire was used as a means of data collection. For the data collected for the analysis, the mean and standard deviation of the research questions were analyzed at the average acceptance level of 2.50, the null hypotheses were verified through the Z-test, and the significance level was set at 0.05. This study's findings show that school boards and principals, especially after elementary school, manage teachers` integrity issues under the Delta Public High School Education Act and Code of Ethics. Among other things, teachers should be encouraged to purchase a copy of the Educational Services Manual to know their rights, their responsibilities to staff, and the fundamental rights of their students.